Germanium-doped optical fiber for real-time radiation dosimetry. (November 2015) - Mizanur Rahman, A.K.M.; Zubair, H.T.; Begum, Mahfuza; Abdul-Rashid, H.A.; Yusoff, Z.; Ung, N.M.; Mat-Sharif, K.A.; Wan Abdullah, W.S.; Amouzad Mahdiraji, Ghafour; Amin, Y.M.; Maah, M.J.; Bradley, D.A.
Abstract: Over the past three decades growing demand for individualized in vivo dosimetry and subsequent dose verification has led to the pursuit of newer, novel and economically feasible materials for dosimeters. These materials are to facilitate features such as real-time sensing and fast readouts. In this paper, purposely composed SiO2 :Ge optical fiber is presented as a suitable candidate for dosimetry. The optical fiber is meant to take advantage of the RL/OSL technique, providing both online remote monitoring of dose rate, and fast readouts for absorbed dose. A laboratory-assembled OSL reader has been used to acquire the RL/OSL response to LINAC irradiations (6 MV photons). The notable RL characteristics observed include constant level of luminescence for the same dose rate (providing better consistency compared to TLD-500), and linearity of response in the radiotherapy range (1 Gy/min to 6 Gy/min). The OSL curve was found to conform to an exponential decay characteristic (illumination with low LED source). The Ge doping resulted in an effective atomic number, Z eff, of 13.5 (within the bone equivalent range). The SiO2 :Ge optical fiber sensor, with efficient coupling, can be a viable solution for in vivo dosimetry, besides a broad range of applications. Highlights: Purposely fabricated Ge doped silica fiber for real-time dose measurements. Constant RL response for dose rates in radiotherapy range. Linearity of RL curve during irradiation using LINAC. RL response comparison between SiO2 :Ge optical fiber and TLD-500.